Another Life of the First Emperor: A Story of Scholarly Biases - Pines, Yuri (JAOS, 2023)
Antony Barbieri-Low presents an engaging and well researched analysis of the changing image of the First Emperor of Qin throughout centuries. Yet the study suffers from insufficient attention to nuances of Chinese political culture, from outright dismission of looted manuscripts (some of which are essential for understanding the Qin), and, primarily, from the author’s own biases. Do these biases suggest the author’s desire to use the First Emperor as a foil in U .S . political debates?